The Hepatoprotective Effect of Leonurine Hydrochloride Against Alcoholic Liver Disease Based on Transcriptomic and Metabolomic Analysis - Wu, Ke-Jia; Liu, Pin-Pin; Chen, Meng-Yuan; Zhou, Meng-Xin; Liu, Xin; Yang, Qing; Xu, Lin; Gong, Zhiyong (Frontiers in Nutrition, 2022)
Excessive alcohol consumption can eventually progress to alcoholic liver disease (ALD). The underlying mechanism of ALD toxicity is primarily associated with oxidative damage. Many alkaloids have been reported to possess potential antioxidative efficacy, while the mechanism of their hepatoprotective activity against ALD is still not clear. In this study, eight alkaloids were selected from a monomer library of Traditional Chinese Medicine and evaluated for their antioxidant activity against ALD by the evaluation of Glutathione (GSH) and Malondialdehyde (MDA). The result suggested that Leonurine hydrochloride (LH) was a potent antioxidant that could reduce alcoholic liver damage. To further investigate the underlying mechanism of LH against ALD, the molecular pathway induced by LH was identified by RNA-seq analyses. Transcriptome data revealed the principal mechanism for the protective effect of LH against ALD might be attributed to the differentially expressed genes (DEGs) of PI3K-AKT, AMPK, and HIF-1 signaling pathways involved in the lipid metabolism. Given the hepatoprotective mechanism of LH is involved in lipid metabolism, the lipid metabolism induced by LH was further analyzed by UHPLC-MS/MS. Metabolome analysis indicated that LH significantly regulated glycerophospholipid metabolism including phosphatidylcholine, 1-acyl-sn-glycero-3-phosphocholine, phosphatidylethanolamine and 1-acyl-sn-glycero-3-phosphoethanolamine in the liver. Overall, this study revealed that the hepatoprotective mechanism of LH against alcoholic liver damage might be associated with the genes involved in glycerophospholipid metabolism.